2016
DOI: 10.1002/fsn3.376
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional quality and sensory acceptability of complementary food blended from maize (Zea mays), roasted pea (Pisum sativum), and malted barley (Hordium vulgare)

Abstract: The aim of this study was to evaluate the effect of blending ratio of malted barley, maize, and roasted pea flour on complementary food quality and sensory acceptability. D‐ Optimal mixture design was used to generate 14 formulations. Each ingredient had 55–90% maize, 20–35% pea and 4–12% malted barley. Pretreatments like debranning of maize, roasting of pea and dehusking of malted barley were done. The three component‐constrained mixture design was conducted using Design‐Expert® 6 (Stat‐Ease). Ash, protein, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
15
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 15 publications
9
15
2
3
Order By: Relevance
“…Low-cost protein-rich ingredients like legumes (also called pulses) are known to upgrade starchy foods (Egounlety, 2002;Mensah & Tomkins, 2003). Studies have shown that optimal blending can optimize the nutritional and sensory quality of complementary foods (Fikiru, Bultosa, Forsido, & Temesgen, 2016;Gebretsadikan, Bultosa, Forsido, & Astatkie, 2015). The second factor is the ratios in which these ingredients are blended.…”
mentioning
confidence: 99%
“…Low-cost protein-rich ingredients like legumes (also called pulses) are known to upgrade starchy foods (Egounlety, 2002;Mensah & Tomkins, 2003). Studies have shown that optimal blending can optimize the nutritional and sensory quality of complementary foods (Fikiru, Bultosa, Forsido, & Temesgen, 2016;Gebretsadikan, Bultosa, Forsido, & Astatkie, 2015). The second factor is the ratios in which these ingredients are blended.…”
mentioning
confidence: 99%
“…Different researchers have also investigated the utilization of flours from dried maize–soy blends (CSBs) in local diets for children and found them well acceptable (Achidi et al., 2016 ; Alamu, Maziya‐Dixon, Popola, Gondwe, & Chikoye, 2016; Amegovu et al., 2014; Cheryan, Mc Cune, Nelson, & Ferrier, 1979; Chukuma et al., 2016; Emire & Buta, 2015; Fikiru, Bultosa, Forsido, & Temesgen, 2016; I‐Brockdorf et al., 2015; Kalimbira, Mtimuni, & Mtimuni, 2004; Kehlet, Kæstel, Hausner, Bredie, & Allesen‐Holm, 2011; Muhimbula, Issa‐Zacharia, & Kinabo, 2011; Ng'ong'ola‐Manani et al., 2014). This study is the first of its kind to formulate and test the acceptability and preference of porridges prepared from smoked and dried fresh maize–soy blends.…”
Section: Discussionmentioning
confidence: 99%
“…In many countries in Sub‐Saharan Africa, rural communities apply traditional malting treatment in food processing (Fasuan et al., 2017; Fikiru, Bultosa, Forsido, & Temesgen, 2016). Traditional malting practices differ between countries and also vary among communities within a country (Bokulich & Bamforth, 2013; Krishnan et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, inadequate information exists on the application of traditional malting technologies practiced in rural areas in processing complementary food formulae. Fundamentally, processing is known to alter sensory properties of food and consumer preference in turn (Fikiru et al, 2016) and these changes depend on the processing method applied (Ariahu, Ingbian, & Ojo, 2009;Laurie & Van Heerden, 2012). To provide an insight into the potential of traditional malting technologies in processing plant-based complementary foods in rural areas, this study examined the effect of a traditional malting technology practiced in Acholi Sub-region of Uganda on: (a) in vitro protein digestibility and bioavailability of iron and zinc; and (b) consumer sensory preference for millet-sesame-soy composite formulae.…”
Section: Introductionmentioning
confidence: 99%